Sleeper pad and elastic sleeper
Patent Information
- Application Number
- JP2023137284
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0012】 本発明の枕木パッドは、コンクリート枕木との接着強度を十分かつ安定して得ることができる。 したがって、本発明の枕木パッドを用いることにより、枕木パッドが剥離しにくく、耐久性に優れた弾性枕木を提供することができる。
Smart Images

Figure 2025031213000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a sleeper pad to be installed on the bottom of a concrete sleeper and an elastic sleeper equipped with the same. [Background technology]
[0002] In railway tracks, rails are generally laid on sleepers. In recent years, sleepers made of concrete have come to be widely used, and sleeper pads made of elastic material are installed on the bottom of the sleepers to prevent ballast from getting under them and to suppress noise and vibrations when railway vehicles are running.
[0003] The sleeper pad, for example, has an anchor member that is embedded in ready-mixed concrete poured into a sleeper mold, and when the ready-mixed concrete hardens with the anchor member embedded, it is joined to the bottom of the concrete sleeper.
[0004] Specifically, Patent Document 1 discloses a sleeper foundation (sleeper pad) in which synthetic resin fibers are formed into a three-dimensional mesh structure (steel wool-like) as a bonding layer (anchor member). Moreover, Patent Document 2 discloses that a hook-and-loop fastener having engaging projections is used as an anchor member. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2011-513610 [Patent Document 2] JP 2015-121028 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the anchor member with a three-dimensional mesh structure as disclosed in Patent Document 1 has an indefinite fiber direction, making it difficult to uniformly impregnate the fresh concrete, and the anchor member is crushed during the impregnation with the fresh concrete, making it difficult to maintain a constant thickness. For this reason, there is a risk that the adhesive strength between the sleeper pad and the concrete sleeper will be insufficient.
[0007] Furthermore, as disclosed in Patent Document 2, when the anchor member is formed of a hook-and-loop fastener, in order to increase the adhesive strength between the sleeper pad and the concrete sleeper, it is necessary to increase the density of the engaging projections, but this leads to narrower gaps between the engaging projections, which makes it difficult for the fresh concrete to be impregnated and makes air voids more likely to occur, resulting in insufficient adhesive strength.
[0008] The present invention has been made in consideration of the above circumstances, and its object is to provide a sleeper pad that can obtain sufficient and stable adhesive strength with a concrete sleeper, and an elastic sleeper equipped with the same. [Means for solving the problem]
[0009] The present invention is based on the discovery that the use of a specified anchor member enables good impregnation of fresh concrete and good impregnation and adhesion of an elastic body, thereby enabling a stable and sufficient adhesive strength to be obtained with respect to a concrete sleeper.
[0010] The present invention provides the following means. [1] A sleeper pad having a pad body made of an elastic material and an anchor member joined to one side of the pad body, wherein the anchor member is an integrated sheet formed by connecting a mesh outer fabric and a mesh inner fabric with a connecting thread that connects the two together. [2] The sleeper pad of [1], wherein the outer and inner linings of the sheet have a mesh opening rate of 40 to 80%. [3] The front and back fabrics of the sheet have a mesh opening area of 0.1 to 60.0 mm 2 / piece, [1] or [2] sleeper pads. [4] A sleeper pad according to any one of [1] to [3], wherein the thickness of the anchor member is 2.0 to 15.0 mm. [5] A sleeper pad according to any one of [1] to [4], wherein the protrusion of the anchor member from the joint surface of the pad body with the anchor member is 0.8 to 13.0 mm. [6] A sleeper pad according to any one of [1] to [5], wherein a ratio of the protrusion of the anchor member to the thickness of the anchor member is 0.10 to 0.95. [7] A sleeper pad according to any one of [1] to [6], wherein the pad body is made of a urethane elastomer. [8] A sleeper pad according to any one of [1] to [7], wherein the elastic body is joined to the back surface of the anchor member by impregnation adhesion to the anchor member. [9] A sleeper pad according to any one of [1] to [8], wherein the constituent material of the anchor member includes any one selected from the group consisting of polyamide, polyester, polyethylene, polypropylene, cellulose, protein, acrylic resin, polyurethane, fluororesin, phenolic resin, polyether ester, polylactic acid, polyimide fiber, glass fiber, carbon fiber, ceramic fiber and metal fiber.
[0011]
[10] An elastic sleeper comprising any one of the sleeper pads according to [1] to [9] and a concrete sleeper joined to the surface of the anchor member of the sleeper pad on the surface side of the sleeper.
[11] The elastic sleeper of
[10] , wherein the concrete sleeper is joined to the anchor member by impregnating adhesion. Effect of the Invention
[0012] The sleeper pad of the present invention can obtain sufficient and stable adhesive strength with the concrete sleeper. Therefore, by using the sleeper pad of the present invention, it is possible to provide an elastic sleeper in which the sleeper pad is less likely to peel off and which has excellent durability. [Brief description of the drawings]
[0013] [Figure 1]1 is a schematic cross-sectional view of an elastic sleeper according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining a sleeper pad in FIG. 1. [Diagram 3] FIG. 3 is a schematic cross-sectional view for explaining the anchor member in FIG. 2. [Figure 4] 1 is a graph showing the relationship between the protrusion and adhesive strength of each anchor member in an adhesion test of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described with reference to the drawings. In addition, the preferred numerical ranges in this specification can be arbitrarily combined with each of the preferred lower limit values and upper limit values.
[0015] The sleeper pad of this embodiment is used for an elastic sleeper as shown in Fig. 1. The elastic sleeper 1 in Fig. 1 has a sleeper pad 2 and a concrete sleeper 3 joined to the surface of the anchor member of the sleeper pad 2 on the surface side.
[0016] 2, the sleeper pad 2 has a pad body 5 made of an elastic body, and an anchor member 4 joined to one side of the pad body 5. The anchor member 4 has a protruding portion 6 exposed from the pad body 5.
[0017] The anchor member 4 in the sleeper pad 2 of this embodiment is an integrated sheet in which a mesh surface 4a and a mesh lining 4b are connected by a connecting thread 4c that connects the two together, as shown in Fig. 3. Thus, the sleeper pad of the present invention is characterized in that the anchor member 4 is a sheet having a three-layer structure consisting of a layer of the mesh surface 4a, a layer of the connecting thread 4c, and a layer of the mesh lining 4b. Since the front layer 4a and the back layer 4b are meshes having openings, impregnation into the inside of the anchor member 4 is easily promoted when the anchor member 4 is impregnated with ready-mixed concrete, and also when the elastic body of the pad body 5 is impregnated and bonded, as described below. Also, since the connecting threads 4c are supported by being sandwiched between the layer of the front layer 4a and the layer of the back layer 4b, the anchor member 4 has elasticity (cushioning properties), and good restoration and retention of thickness when impregnated under pressure is obtained. Therefore, according to the anchor member 4 having the above-mentioned configuration, the anchor member 4 is not crushed and the protruding portion 6 is not pushed down during the impregnation of the fresh concrete, and the impregnation thickness can be ensured and the concrete can be uniformly impregnated.
[0018] The mesh outer fabric 4a and the mesh inner fabric 4b are not particularly limited as long as they are in a mesh shape having a plurality of openings, and examples thereof include woven fabric, knitted fabric, nonwoven fabric, resin punching, etc. The outer fabric 4a and the inner fabric 4b may be the same or different. The shape of the openings of the mesh is not particularly limited, and examples thereof include a triangle, a rectangle, a hexagon, a circle, an ellipse, etc. The opening shapes of the mesh may be the same or different between the outer layer 4a and the inner layer 4b.
[0019] The anchor member 4 is preferably formed as a three-dimensional knitted fabric in which a knitted mesh outer fabric 4a and a knitted mesh inner fabric 4b are connected by a connecting thread 4c. It is preferable that the anchor member 4 has good elasticity and is not crushed when impregnated with fresh concrete, while ensuring a sufficient impregnation thickness and firmly integrating the front layer 4a and the back layer 4b.
[0020] The connecting thread 4c may have, for example, a pillar structure, a truss structure, a cross structure, or a combination of these structures between the front layer 4a and the back layer 4b in the cross section in the thickness direction of the anchor member 4. From the viewpoint of forming a layer that is unlikely to be crushed and can ensure a sufficient impregnation thickness when impregnating with fresh concrete, it is preferable that the connecting thread 4c is a monofilament that connects the front layer 4a and the back layer 4b in a structure that combines a pillar structure and a cross structure. Since the front surface 4a and the back surface 4b are meshes with openings, when the anchor member 4 is impregnated with ready-mixed concrete, and when the elastic body of the pad body 5 is impregnated and bonded as described below, the front surface 4a and the back surface 4b exert an anchoring effect in the surface direction of the sheet of the anchor member 4. In addition, the connecting thread 4c that integrates the front surface 4a and the back surface 4b exerts an anchoring effect in the thickness direction of the sheet of the anchor member 4, so that the synergistic effect of both anchoring effects provides sufficient and stable adhesive strength between the sleeper pad 2 and the concrete sleeper.
[0021] The opening ratio of the mesh of the surface layer 4a is preferably 40 to 80%, more preferably 45 to 75%, and even more preferably 48 to 72%, from the viewpoint of allowing the anchor member 4 to maintain the surface shape of the projection 6 and to be easily impregnated with fresh concrete. From the viewpoint of good adhesion density with the pad body 5, the opening rate of the mesh of the lining 4b is preferably within the same numerical range as that of the outer layer 4a, preferably 40 to 80%, more preferably 45 to 75%, and even more preferably 48 to 72%. The mesh opening ratio may be the same or different between the outer layer 4a and the inner layer 4b.
[0022] The surface layer 4a has an opening area of the mesh of preferably 0.1 to 60.0 mm2 so that the anchor member 4 can be easily impregnated with fresh concrete and sufficient adhesive strength between the sleeper pad 2 and the concrete sleeper 3 can be obtained by the anchor effect. 2 / piece, more preferably 0.2 to 58.0 mm 2 / piece, more preferably 0.5 to 55.0 mm 2 / piece. From the viewpoint of good adhesion density with the pad body 5, the opening area of the mesh of the lining 4b is preferably in the same numerical range as that of the outer layer 4a, and is preferably 0.1 to 60.0 mm 2 / piece, more preferably 0.2 to 58.0 mm 2 / piece, more preferably 0.5 to 55.0 mm 2 / piece. The opening area of the mesh may be the same or different between the outer layer 4a and the inner layer 4b.
[0023] The mesh opening area S is the area per opening calculated based on the actual size. The mesh opening rate is the ratio of the total area occupied by openings per unit area, and the opening area S [mm 2 / piece] and the specified area S 1 [mm 2 ] is multiplied by the number of openings per unit area S 1 [mm 2 Specifically, it can be calculated by the method described in the Examples.
[0024] The thickness of the anchor member 4 may be any thickness that provides sufficient adhesive strength between the sleeper pad 2 and the concrete sleeper 3 through the anchor effect, and is preferably 2.0 to 15.0 mm, more preferably 3.0 to 12.0 mm, and even more preferably 4.0 to 10.0 mm.
[0025] The protrusion 6 of the anchor member 4 in the pad body 5 is preferably 0.8 to 13.0 mm, more preferably 1.0 to 12.0 mm, and even more preferably 1.2 to 10.0 mm, from the viewpoint of impregnating with fresh concrete and obtaining sufficient adhesive strength between the sleeper pad 2 and the concrete sleeper 3 through the anchor effect.
[0026] From the same viewpoint, the ratio of the projection 6 of the anchor member 4 to the thickness of the anchor member 4 is preferably 0.10 to 0.95, more preferably 0.40 to 0.80, and further preferably 0.50 to 0.70.
[0027] Examples of materials constituting the anchor member 4 include polyamide, polyester, polyethylene, polypropylene, cellulose, protein, acrylic resin, polyurethane, fluororesin, phenolic resin, polyether ester, polylactic acid, polyimide fiber, glass fiber, carbon fiber, ceramic fiber, metal fiber, etc. Since the anchor member 4 comes into contact with concrete, it is preferable that it has alkali resistance, and from the viewpoints of appropriate elasticity and ease of handling, etc., among these, polyamide, polyester, and polyethylene are preferable, and nylon, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), etc. are suitably used.
[0028] The anchor member 4 may be made of the same constituent material for the outer fabric 4a, the inner fabric 4b, and the connecting thread 4c, or may be made of different constituent materials for any or all of them. For example, the outer fabric 4a, the inner fabric 4b, and the connecting thread 4c may be made of nylon, or the outer fabric 4a and the inner fabric 4b may be made of polyester, and the connecting thread 4c may be made of nylon. The constituent materials of the outer fabric 4a, the inner fabric 4b, and the connecting thread 4c may be appropriately selected according to the constituent material of the pad body 5 so as to obtain a good bonding strength. The anchor member 4 may be a commercially available sheet.
[0029] The pad body 5 is made of an elastic body so as to satisfy the standard of the spring constant of the sleeper pad 2 required for suppressing noise and vibration during the running of a railway vehicle. Examples of the elastic body include rubbers such as styrene butadiene rubber (SBR) and ethylene propylene diene rubber (EPDM), polyurethane, etc., from the viewpoint of weather resistance, etc., and foams are preferred from the viewpoint of good elasticity and vibration resistance, etc. As the elastic body, urethane elastomers are preferred.
[0030] The anchor member 4 and the pad main body 5 may be joined using an adhesive, but from the viewpoint of strong joining between them, it is preferable that the elastic body constituting the pad main body 5 is joined to the lining surface of the anchor member 4 by impregnation adhesion to the anchor member 4. In Figures 1 and 2, part D is a part of only the elastic body (not impregnated in the anchor member), and part A is a part of the anchor member 4 where the elastic body is impregnated and adhered.
[0031] From the viewpoint of stably supporting the concrete sleeper 3, the pad body 5 is preferably joined to the entire surface of the backing side of the anchor member 4. The sleeper pad 2 is cut to the required size as appropriate for use depending on the size of the concrete sleeper 3 to be joined.
[0032] As described above, the anchor member 4 in the sleeper pad 2 of this embodiment has a layer of the surface layer 4a and a layer of the lining layer 4b on both outer layers. Therefore, compared with the case where the anchor member 4 has only the surface layer 4a and the lining layer 4b on one side, or the case where the anchor member 4 does not have the surface layer 4a and the lining layer 4b (for example, steel wool type), even if the impregnation depth of the elastic body in the anchor member 4 is small, sufficient adhesive strength can be obtained between the anchor member 4 and the pad main body 5 made of the elastic body, and a sleeper pad 2 that satisfies the standard for the spring constant can be obtained.
[0033] The thickness of the pad body 5 can be appropriately set according to the desired spring constant. When the pad body 5 is formed by bonding an elastic body to the anchor member 4 by impregnation adhesion, the thickness of the pad body 5 is preferably thicker than the impregnation thickness of the elastic body in the anchor member 4.
[0034] The sleeper pad 2 of this embodiment can be manufactured, for example, as follows. A specified polyurethane raw material liquid is poured into a specified mold, and the back surface of the anchor member 4 is immersed in it to a specified depth and cured. By demolding, a sleeper pad 2 is obtained in which the pad body 5 made of urethane elastomer and the back surface of the anchor member 4 are impregnated and bonded (part A), and the surface side of the anchor member 4 has a protrusion 6. As the polyurethane raw material, for example, a known raw material for producing a urethane elastomer can be used.
[0035] The elastic sleeper 1 of this embodiment includes a sleeper pad 2 and a concrete sleeper 3 joined to the surface of the anchor member 4 of the sleeper pad 2 on the surface side. The elastic sleeper 1 equipped with the sleeper pad 2 of this embodiment has good durability because the sleeper pad 2 is not easily peeled off.
[0036] From the viewpoint of obtaining a sufficient adhesive density with the sleeper pad 2, the concrete sleeper 3 is preferably joined to the anchor member 4 by impregnation adhesion. The elastic sleeper 1 can be manufactured, for example, using the sleeper pad 2 of this embodiment as follows. Ready-mixed concrete is poured into a specified sleeper mold, and the projection 6 on the surface side of the sleeper pad 2, which has been cut to fit the size of the sleeper bottom, is immersed in the ready-mixed concrete and allowed to harden. The hardened product is demolded to obtain an elastic sleeper 1 in which the concrete sleeper 3 is impregnated and bonded to the anchor member 4 of the sleeper pad 2. In Figure 1, part C is the part containing only concrete (not impregnated in the anchor member), and part B is the part in which the projection 6 of the sleeper pad 2 is impregnated and bonded with concrete. The elastic sleeper 1 obtained in this manner is well held with almost no reduction in the thickness of the anchor member 4, the anchor member 4 exerts a good anchoring effect on both the pad body 5 and the concrete sleeper 3, and the sleeper pad 2 and the concrete sleeper 3 have sufficient adhesive strength. EXAMPLES
[0037] The present embodiment will be described below based on examples, but the present invention is not limited to the following examples.
[0038] [Manufacturing sleeper pads] Using various anchor members, sleeper pads of the configuration shown in Figure 2 were manufactured. Details of the various anchor members used are shown in Table 1. The mesh opening area S of the outer and inner lining of the anchor member was calculated based on the dimensions of the opening measured with a ruler. The mesh opening rate P was calculated based on the dimensions of the outer or inner lining, 50 mm long x 50 mm wide (area 2500 mm 2 The numerical aperture N per unit area was measured visually and calculated using the following formula: P[%]=S[mm 2 / piece]×N / 2500[mm 2 ] x 100
[0039] [Table 1]
[0040] In Table 1, "AKE65714", "AKE64036" and "AKE69440" in the types of anchor members are part numbers of "Fusion (registered trademark)", a product name manufactured by Asahi Kasei Advance Corp. In anchor members (A), (B) and (C), the connecting thread is a monofilament, and the outer fabric and the lining fabric are connected by the connecting thread in a structure that combines a pillar structure and a cross structure. The anchor members (A1) and (A2) are formed by cutting the outer or inner layer of the anchor member (A) with scissors to expose the connecting thread. The anchor member (D) is formed into a three-dimensional mesh structure (steel wool-like) from polypropylene (PP) fibers (fiber diameter 0.4 mm).
[0041] (Examples 1 to 3 and Comparative Examples 1 to 3) Liquid T and Liquid R were each charged into the raw material tank of a low-pressure injector ("A-240", manufactured by Toho Machinery Co., Ltd.), discharged at 50°C, and mixed and stirred with a stirring blade (3000 rpm) to prepare a polyurethane raw material liquid. Note that liquid T in the urethane raw material liquid (two-component type) is a polyisocyanate prepolymer, and liquid R is a mixture of polyether polyol, tertiary amine catalyst, silicone-based defoamer, phosphate-based flame retardant, and carbon black. The polyurethane raw material liquid was poured into a mold (made of aluminum, 1015 mm long x 200 mm wide) at 55°C that had been coated with a release agent, to a depth (thickness) of 16 mm. This mold was covered with a mold lid to which an anchor member had been attached, and the protrusion was adjusted with a spacer. The anchor member was left to stand for 30 minutes with the back side of the anchor member immersed in the urethane raw material liquid to harden. The material was removed from the mold and cured at room temperature (25°C) for 24 hours to obtain a sleeper pad. Sleeper pads were manufactured with various projection lengths.
[0042] [Manufacturing elastic sleeper specimens] Using each of the sleeper pads produced above, specimens for elastic sleeper adhesion tests were produced. In the specimens, the hardened mortar was used as a substitute for concrete sleepers. 4.7 kg of premixed mortar ("Tite Glaster", manufactured by Manol Co., Ltd.) was mixed with 0.99 kg of water and mixed and stirred with a drill mixer to prepare the mortar. The mixed mortar was poured into a 200mm long x 200mm wide mold to a depth of 60mm, and a sleeper pad cut to 200mm long x 200mm wide was placed over the surface. The mold was vibrated to degas the inside of the sleeper pad and the interface with the mortar, and then left to harden for 60 minutes. The mold was removed and cured at room temperature (25°C) for 24 hours to obtain a test specimen.
[0043] [Adhesion test] Using a hole saw (inner diameter 50 mm) attached to a bench drill press, four spaced cuts (30 mm deep) were made on the sleeper pad side of the obtained test specimen, and a test jig (made of high-tensile aluminum, bottom: 50 mm diameter circle, top: gripping protrusion) was attached to the circular part inside the cut with adhesive (Aron Alpha (registered trademark), manufactured by Toagosei Co., Ltd.) and left to stand for at least 24 hours. The specimen with the test jig attached was fixed to a tensile testing machine (Autograph AG-I, Shimadzu Corporation) with the test jig side facing up. An attachment was attached to the test jig, and it was pulled vertically (tensile speed 0.03±0.02MPa / sec) to measure the load at the yield point. The load at the yield point [N] was calculated based on the adhesion area (1963 [mm 2 ]=25×25×π) was used as the adhesive strength (average value of four points).
[0044] If the adhesive strength between the test specimen's sleeper pad and mortar is 0.5 MPa or more, it is a sufficient adhesive strength, and it can be said that the sleeper pad and the concrete sleeper are unlikely to peel off, and a good elastic sleeper can be obtained. Therefore, the evaluation standard for good adhesive strength in the adhesive test was set at 0.5 MPa or more.
[0045] The adhesive strength of the anchor members of each of the Examples and Comparative Examples was measured when the protrusion was changed. Figure 4 shows a graph of the relationship between the protrusion and adhesive strength of each anchor member. As can be seen from the graph in FIG. 4, the sleeper pads (Examples 1 to 3) using the anchor members of this embodiment had sufficient adhesive strength with mortar regardless of the length of the anchor member protruding. On the other hand, an anchor member (Comparative Example 1) without an outer fabric and with the connecting thread exposed on the outer fabric side (two-layer structure of connecting thread and lining) did not obtain adhesive strength that met the standard. An anchor member (Comparative Example 2) without a lining and with the connecting thread exposed on the lining side (two-layer structure of connecting thread and outer fabric) also did not obtain adhesive strength that met the standard. An anchor member (Comparative Example 3) with an overall three-dimensional mesh structure (single-layer structure) also did not obtain adhesive strength that met the standard.
[0046] Based on the results of observing each specimen and its fracture state after the adhesion test, the following considerations can be made. In Comparative Example 1, the anchor member was impregnated with mortar with the connecting threads crushed or tilted, and there were some parts where the connecting threads were cut. For this reason, it is considered that the anchor effect of the anchor member on the mortar was insufficient, and sufficient adhesive strength was not obtained. In Comparative Example 2, the connecting threads were crushed or tilted, the polyurethane raw material liquid impregnated in the anchor member was partially seeped out to the surface and hardened, and the thickness of the anchor member itself was reduced. For this reason, the length of the protrusion for impregnating and bonding the mortar was insufficient, and sufficient adhesive strength was not obtained due to the insufficient anchor effect. In Comparative Example 3, since the anchor member did not have a structure equivalent to the outer and inner linings and the fiber direction was indefinite, it is considered that the anchor effect was insufficient for both the pad body and the mortar, and sufficient adhesive strength was not obtained.
[0047] In contrast, in the anchor members of Examples 1 to 3, the connecting threads were not crushed or tilted, the thickness of the anchor member in the test specimen was not reduced, and the adhesive interface between the pad body and the mortar was attached to the connecting thread part almost parallel to the bottom surface of the pad body. It is considered that the front and back fabrics provided a good anchor effect to both the pad body and the mortar, and adhesive strength that met the standard was obtained. [Explanation of symbols]
[0048] 1 Elastic sleeper 2 Sleeper Pads 3 Concrete sleepers 4 Anchor members 4a Outer material 4b Lining 4c Connecting thread 5 Pad body 6. Outcome
Claims
1. This sleeper pad has a pad body made of an elastic material and an anchor member joined to one side of the pad body, and the anchor member is an integrated sheet formed by connecting a mesh outer layer and a mesh inner layer with a connecting thread that connects the two together.
2. The sleeper pad according to claim 1, wherein the surface and backing of the sheet have a mesh opening rate of 40 to 80%.
3. The front and back fabrics of the sheet have a mesh opening area of 0.1 to 60.0 mm 2 2. The sleeper pad of claim 1, wherein the sleeper pad comprises:
4. The sleeper pad of claim 1, wherein the thickness of the anchor member is 2.0 to 15.0 mm.
5. 2. The sleeper pad according to claim 1, wherein the projection of the anchor member from the joint surface of the pad body with the anchor member is 0.8 to 13.0 mm.
6. 2. The sleeper pad according to claim 1, wherein the ratio of the projection of the anchor member to the thickness of the anchor member is 0.10 to 0.
95.
7. 2. The sleeper pad according to claim 1, wherein the pad body is made of a urethane elastomer.
8. 2. The sleeper pad of claim 1, wherein the elastic body is bonded to a backing surface of the anchor member by impregnation adhesion to the anchor member.
9. The sleeper pad of claim 1, wherein the constituent material of the anchor member includes any one selected from the group consisting of polyamide, polyester, polyethylene, polypropylene, cellulose, protein, acrylic resin, polyurethane, fluororesin, phenolic resin, polyether ester, polylactic acid, polyimide fiber, glass fiber, carbon fiber, ceramic fiber and metal fiber.
10. An elastic sleeper comprising: a sleeper pad according to any one of claims 1 to 9; and a concrete sleeper joined to the surface side surface of the anchor member of the sleeper pad.
11. 11. The resilient sleeper of claim 10, wherein the concrete sleeper is bonded to the anchor member by impregnation adhesion.
Citation Information
Patent Citations
Railway sleeper foundations
JP2011513610A
Pad for sleeper
JP2015121028A